Analysis of Cross Site Request Forgery (CSRF) Attacks on West Lampung Regency Websites Using OWASP ZAP Tools - Ilham Firman Ashari; Vina Oktarina; Ringgo Galih Sadewo; Salman Damanhuri (ISB Atma Luhur, 2022)
Technological developments in the field of increasingly advanced computers and networks have caused many organizations to use web applications to provide business services. With the increasing popularity of the internet, the number of cyber-attacks has also increased. To overcome these negative impacts, the role of network security is very necessary. The Cross Site Request Forgery (CSRF) method is a penetration technique aimed at exploiting website security vulnerabilities and there is one tool commonly used to find security vulnerabilities on websites, namely OWASP ZAP. The research has succeeded in proving security vulnerabilities on the website of the West Lampung district by conducting attack simulations. From the results of the experiment, it was found that there were 12 alerts with low risk on the website of West Lampung Regency. In 12 alerts there are 53 URL pages that are vulnerable to attack.